Determinants of financial statements integrity - Reni Yendrawati; Mohammad Farid Hidayat (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This research aims to find out the influence of corporate governance measured by institutional ownership, managerial ownership, audit committee, and independent commissioner, as well as the influence of accounting firm specialization and audit tenure on the integrity of financial statements. The population of this research was the service companies in the infrastructure, utilities, and transportation sectors listed at IDX during the period 2015-2018. The sampling was done using purposive sampling method which collected 21 companies. The data analysis method used was multiple linear regression. The research findings reveal that institutional ownership, managerial ownership, independent commissioner, and accounting firm specialization have positive influences on the integrity of financial statements, while audit committee and audit tenure do not have significant influences on the integrity of financial statements.